Up Up and Away - McNamara, Noela (LiNQ (Literature in North Queensland), 2016)
Noela McNamara reviews: Jude Aquilina, On a Moon Spiced Night. Wakefield Press, ISBN 1 86254 640 1 Rrp. 19.95 Barbara De Franceschi, Lavender Blood. Seaview Press, ISBN 1 74008 287 7 Rrp. 25.00